Site and management effects on grain yield and yield variability of rainfed lowland rice in the Kilombero flood plain of Tanzania - Kwesiga, Julius; Grotelüschen, Kristina; Neuhoff, D.; Senthilkumar, Kalimuthu; Döring, T.F.; Becker, M. (MDPI, 2019)
In East Africa, smallholder farmers produce rainfed lowland rice mainly in floodplains. Low nitrogen contents of the predominant Fluvisols and highly variable hydrological conditions result in low yields and large yield variations, and hence, result in high production risks for farmers. We investigated crop management strategies aimed at increasing yield and reducing yield variability. The field trials were carried out in the Kilombero floodplain near Ifakara in Tanzania, in three hydrological zones (potentially drought-prone fringe, favorable middle and submergence-prone center positions) over three years. The study compared farmers’ management practices (no field levelling and bunding, no fertilizer input), with the effect of bunding and levelling alone, or in combination with mineral N use at 0 (bunding), 60 (recommended rate) and 120 kg + 60 kg PK ha−1 (attainable yield). Rice mean grain yields (averaged over the four treatments) were higher in the fringe (6.5 t ha−1) and the middle (5.7 t ha−1) than in the center positions (4.6 t ha−1). Farmers’ practice resulted in lowest yield (3.0 t ha−1) and highest yield variability, with an adjusted coefficient of variation (aCV) of up to 91% between fields, years and positions. Simple bunding of the plots and field levelling increased yields by 40% above farmers’ practice, particularly in the fringe and middle positions, while reducing yield variation (aCV of 36–61%). Mineral N application resulted in the highest yields (7.0 t ha−1) and further reduced yield variation (aCV of 14–27%). However, only in bunded fields of the floodplain fringe rice could benefit from N application beyond 60 kg ha−1, while mineral N use efficiency was lower in middle and center positions. Improved crop management options are most beneficial in floodplain fringe positions, where they can increase yields and reduce production risks. Due to low yield, high production risks and poor responsiveness to management interventions, the center may be taken out of rice production and could be considered for future use as protection zones.